DENSITAS TANGKASI (TARSIUS SPECTRUM) DI KAWASAN HUTAN KOTA DESA KUWIL KABUPATEN MINAHASA UTARA - Sandy, Jhon Ismail; Saroyo, Saroyo; Wahyudi, Lalu (PHARMACON, 2019)
ABSTRACT The Kuwil Village Forest City holds an endemic species of Tangkasi (Tarsier spectrum). The condition of forests that characterizes primary forests makes the stems remain in the forest area still status is urban forest. The area of the City Forest of the Kuwil Village is ± 43 ha with a total sampling area of 0.0275 km2 or 2.75 ha with the number of plots installed putting together 14 plots that form a circle with a radius of 25 m. Data was collected in the morning at 05.00-06.15 WITA. Based on the research results obtained a total of duet calls at the location obtained 18 duet calls with a total of 2627 tails / km2 or 26.27 tails / ha which indicates a high population density in urban forest areas. Kuwil City Forest has a variety of potential wildlife that can be processed for conservation of its sustainability. Wildlife conservation can be useful in the future so that it can be used as the development of wildlife utilization both for recreation, natural attractions, and research development. Key words: Kuwil Village, Tangkasi, Kuwil Urban Forest, Density of Tarsier, Conservation. ABSTRAKHutan Kota Desa Kuwil menyimpan satwa endemik tangkasi (Tarsius spectrum). Kondisi hutan yang mencirikan hutan primer membuat tangkasi tetap tinggal di kawasan hutan meskipun statusnya adalah hutan kota. Luas area Hutan Kota Desa Kuwil adalah ± 43 ha dengan luas area total pengambilan sampel adalah 0,0275 km2 atau 2,75 ha dengan jumlah plot yang di pasang berjumlah 14 plot berbentuk lingkaran dengan jari-jari 25 m. Pengambilan data dilakukan pada pagi hari pukul 05.00-06.15 WITA. Berdasarkan hasil penelitian diperoleh total duet call di lokasi berjumlah 18 duet call dengan jumlah 2627 ekor/Km2 atau 26,27 ekor/ha yang menunjukkan kepadatan populasi tangkasi pada kawasan hutan kota jumlah populasi yang tinggi. Hutan Kota Kuwil mempunyai beragam potensi satwaliar yang dapat diolah untuk memelihara kelestariannya. Konservasi satwaliar dapat berguna kedepannya agar dapat digunakan sebagai pengembangan pendayagunaan satwaliar baik untuk rekreasi, objek wisata alam, dan pengembangan penelitian. Kata kunci: Desa Kuwil, Tangkasi, Hutan Kota kuwil, Densitas Tangkasi, konservasi.